Comparative Anatomy of Roots and Leaves in Epiphytic and Terrestrial Orchids: Insights into Adaptations and Ecological Strategies - Mawinei, Naiya; Paramitha, Qeva (Institute for Law and Economics Studies, 2024)
Orchids are renowned for their exquisite beauty and remarkable diversity, with over 25,000 species distributed across a wide range of habitats worldwide. Understanding the anatomical adaptations of orchids to different environmental conditions is crucial for elucidating their ecological and evolutionary strategies. In this study, we conducted a comparative analysis of orchid anatomy, focusing on roots and leaves in epiphytic and terrestrial species. Through meticulous examination and comparison of anatomical features, we revealed distinctive morphological differences that reflect the adaptive responses of orchids to their respective habitats. Epiphytic orchids exhibited specialized root structures such as the velamen and succulent leaves, optimizing water absorption and photosynthesis in the canopy. In contrast, terrestrial orchids displayed extensive root systems and broad leaves, enhancing nutrient uptake and light capture in shaded environments. These findings provide valuable insights into the ecological dynamics and evolutionary history of orchids, highlighting their significance as model organisms for studying plant adaptation and biodiversity conservation. By leveraging insights from orchid research, we can develop targeted conservation strategies to protect these iconic plants and their ecosystems in the face of environmental change and human activities.